2002
DOI: 10.1046/j.0014-2956.2001.02664.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence study of the high pressure‐induced denaturation of skeletal muscle actin

Abstract: ] made a thorough study of the e ect of pressure on G-and F-actins. However, all of the measurements in their study were made after the release of pressure. In the present experiment in situ observations were attempted by using eATP to obtain further detailed kinetic and thermodynamic information about the behaviour of actin under pressure. The dissociation rate constants of nucleotides from actin molecules (the decay curve of the intensity of¯uorescence of eATP-G-actin or eADP±F-actin) followed ®rst-order kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…Exerting pressure on a filamentous structure can lead to destruction of noncovalent bonds, loss of nucleotide, and, subsequently, filament depolymerization, as shown for actin and ParM filaments. 11,17 AlfA filaments disintegrated almost linearly with rising pressure, with complete disintegration reached at about 1700 bar (Fig. S4b and c).…”
Section: Steady-state Dynamicsmentioning
confidence: 80%
See 1 more Smart Citation
“…Exerting pressure on a filamentous structure can lead to destruction of noncovalent bonds, loss of nucleotide, and, subsequently, filament depolymerization, as shown for actin and ParM filaments. 11,17 AlfA filaments disintegrated almost linearly with rising pressure, with complete disintegration reached at about 1700 bar (Fig. S4b and c).…”
Section: Steady-state Dynamicsmentioning
confidence: 80%
“…5d). The behavior of AlfA filaments under pressure differed both from that of F-actin, which was a stable filament until about 2000 bar, 17 and from that of ParM, which dissociated rapidly at low pressures around 400-500 bar. 11…”
Section: Steady-state Dynamicsmentioning
confidence: 91%
“…[10] Moreover,inv itro studies have shown that pressure shifts the equilibrium of the monomer-to-filament transformation of actin towards the monomeric state of the protein, and this equilibrium shift has been found to be species-dependent. [11][12][13][14][15] In this study,w es et out to quantitativelye xplore the kinetics of the polymerization reactiono fa ctin, focusing on the early events, as af unction of temperature and pressure to gain am echanistic understanding of their limitations on actin assembly.H igh-pressure stopped-flow measurements at selected temperatures enabled us to determine the activationv olume, DV°,o ft he process, whichi nt urn sheds light on the inhibitory process of pressure. Moreover,i nc ombination with quantitative Monte Carlo simulations of the polymerization process, we were able to elucidate which features and kinetic parameters are essential in determining their kinetic stability.…”
Section: Introductionmentioning
confidence: 99%
“…Exerting pressure on a filamentous structure, can lead to the destruction of noncovalent interactions, loss of nucleotide and subsequently to filament depolymerization, as shown for actin and ParM filaments (24,8). MreB filaments were stable unto about 2000 bar after which they disintegrated (Fig.…”
Section: Mreb Sheet Morphology-in Vitromentioning
confidence: 99%